Implementasi Pembelajaran Inkuiri Terbimbing Berbasis Potensi Lokal Sebagai Upaya Meningkatkan Sikap Peduli Lingkungan Siswa - Dini Annisha (LPPM Politeknik Pratama, 2023)
The implementation of guided inquiry learning based on local potential is a process in increasing understanding and knowledge in general in students with environmental problems which in the end will lead to an attitude of concern for environmental sustainability. This study aims to determine the effectiveness of guided inquiry learning based on local potential to assess environmental care attitudes. The research method uses a nonrandomized control group pretest-posttest design using two class groups, namely the experimental class and the control class. The research was conducted on students at SMK Negeri 6 on grade XI students of SMK Negeri 6 Fisheries and Marine Lhokseumawe. The subjects of the study amounted to 40 students. The data collection instrument is in the form of a questionnaire of environmental care attitudes. Data analysis techniques in effective tests use Anacova analysis techniques. Based on the results of the study, it is known that the experimental class had an average correction of 73.04 with an increase of 27.4% compared to the control class with an average correction of 72.14 and an increase of only 10.4%. Thus, this research proves that the implementation of guided inquiry learning based on local potential is significantly effective in improving students' environmental care attitudes.